Long way home by - Morpurgo, Michael (Egmont, 2015)
George has already made up his mind to run away, back to the children's home. None of the previous families have wanted him. Why should the Dyers be any different? But George begins to feel at ease with Tom Dyer and his sister Storme, even happy, and changes his mind. He could even feel at home with them - couldn't he?